An Analysis Project Quality Management Case: Housing Development Project at Griya Cempaka Residential Tambun (The Indonesian Journal of Business Administration, 2015)
Abstract– Griya Cempaka Residential Tambun is a residential project which developed by PT. Daya Propindo Abadi. The problem of Griya Cempaka Residential is low quality house, the house that was build has oblique shapes and use of poor material. This problem solved by analyzing the project using qualitative analysis and use project quality management tools namely Fishbone diagram and Work Breakdown Structure. This final project objective is to suggest a project quality management by processing information from interview and project’s documents to solve project problems that could be used by developer to manage their house quality especially in Griya Cempaka Residential project. The analysis of project quality management on this project resulted in two implementation plans. The first implementation plan is create a complete house specification and working drawing that should be used in project contract, so it could achieve the expected quality. To support it, the second implementation plan is create work guidance and control that could be used by developer especially project inspector and contractor especially foreman to control and report the progress of the house as good physical form, so it could minimize additional effort of low quality.Keywords: project quality management, work guidance and control, house quality